Molten salt reactor core simulation with PROTEUS. (1st June 2020) - Fei, T.; Feng, B.; Heidet, F.
Highlights: The High-fidelity code PROTEUS was used to simulate a Molten Salt Reactor. The results (k-eff and flux distribution) from PROTEUS and OpenMC agree well. The precursor drift model in PROTEUS-Nodal showed the reduction in k-eff. Abstract: The Nuclear Energy Advance Modeling and Simulation Program (NEAMS) of the US Department of Energy (DOE) aims to develop advanced simulation tools to aid the development of advanced nuclear technologies. The high-fidelity PROTEUS code was developed in the NEAMS program for reactor physics analysis. This paper tests the applicability of the PROTEUS code to simulate a Molten Salt Reactor (MSR). The OpenMC code based on the Monte Carlo Method was employed to generate the cross sections and to provide stochastic solutions for verification. The PROTEUS code was successfully employed to simulate the steady-state performance of an MSR represented by the ThorCon core design. The 2D lattice, 2D core, and 3D full core calculations performed by PROTEUS show good agreement with that predicted by OpenMC. For the nodal option within PROTEUS, the precursor drift model was also tested, and this effect resulted in a reduction of the k-eff by 300 pcm.